Study of gestational trophoblastic diseases at a tertiary care hospital in India - Antaratani, Ramalingappa C.; M., Shruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gestational trophoblastic disease refers to the heterogeneous group of interrelated lesions that arises from abnormal proliferation of placental trophoblasts. GTNs are among the rare human tumours that can be cured even in the presence of widespread dissemination. Although GTNs commonly follow a molar pregnancy, they can occur after any gestational event, including induced or spontaneous abortion, ectopic pregnancy, or term pregnancy. The study was conducted to know the incidence of different types of gestational trophoblastic diseases in the local population and the percentage of people ultimately requiring chemotherapy. Methods: The retrospective analysis of case record of 124 women with a diagnosis of GTD admitted to Karnataka Institute of Medical Sciences Hubli between November 2008 to November 2017. Results: A total of 124 cases of GTD were reviewed. Hydatidiform mole was diagnosed in 91 patients; of those experienced spontaneous remission after evacuation. 04 patients had persistent gestational trophoblastic Neoplasia and 13 cases of invasive mole (GTN) 1 case of epitheloid trophoblastic tumors and 15 cases of choriocarcinoma 99 (80%) had low-risk GTN, 25 (20%) had high-risk GTN. Conclusions: Hydatidiform mole was found to be the most common form of gestational trophoblastic diseases. Majority of the cases got cured by simple surgical evacuation. During the course of our study some rare cases of gestational trophoblastic diseases were noted. Patients’ compliance for serial follow up is a highly challenging task in developing countries. Registration of women with GTD represents a minimum standard of care.